The Phenomenon of Development Misyar Marriage from the Perspective of Islamic Law and Human Rights - Arinda Putri.J, Pramai Shella; Radhi Anadi, Yandri; Deuraseh, Nurdeng (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
Misyar marriage is one of several Muslim terms in the Middle East. Due to the evolution of life and society, this marriage is a significant phenomenon in Islamic circles. Misyar marriage is performed by a man under the correct contract and conditions, where both parties must give up some rights that are incomparable with the conditions of other marriages Misyar marriage demands that women relinquish certain rights ordinarily associated with marriage, which raises concerns for human rights, particularly those governing discrimination against women. On the contrary, human rights uphold the values of rights and dignity regardless of gender, particularly for women who should receive the same treatment and rights as men, one of which is discussed in the conventions on eradicating all forms of discrimination against women and the rights of the child. This study examines the phenomenon of Misyar marriage through the lens of Islamic law and human rights, employing legal doctrinal or normative research methods, a statutory approach, and a historical perspective. The findings of this study indicated that Misyar marriage differs from other marriages and has a connection to human rights, particularly women's rights to marry. Some scholars believe that this Marriage is permissible and valid. However, according to the following opinion, Misyar marriage is prohibited. This is a violation of international law and not a violation of human rights because the conditions for marriage are not satisfied.